Analysis of Student Challenges in Microteaching Practice in Early Elementary School Grades - La Ode Fajrul Islam Sabti; Jufri Agus; Muhammad Yusnan (Institute Journal and Publication Muhammadiyah University of Buton, 2025)
Microteaching practice is a crucial strategy for equipping prospective teachers with applicable pedagogical competencies. However, in its implementation within early grade classrooms of primary schools, students often face various complex challenges. This study aims to analyze the main difficulties encountered by students of the Primary School Teacher Education (PGSD) Program at Universitas Muhammadiyah Buton during microteaching activities, particularly in the fourth semester course. Employing a qualitative research approach, data were collected through in-depth interviews, participatory observation, and documentation. The data were gathered from students currently undertaking microteaching and analyzed thematically. The findings reveal that students struggle to develop contextual and practical lesson plans (RPP), lack the ability to deliver material in an engaging and communicative manner, and demonstrate limited use of instructional media appropriate to the characteristics of early-grade learners. These challenges indicate a gap between theoretical understanding and practical classroom application. Observational and interview data further support the notion that students are not yet fully capable of translating pedagogical theories into meaningful classroom activities for young children. This study concludes that enhancing the quality of microteaching guidance at the university level is essential, particularly in strengthening students' practical and reflective teaching skills. The research provides important contributions toward the development of more contextual and adaptive teacher training programs that respond to the instructional needs of early grade primary education.